Satisfaction gap in public sector financial reporting - Krambia-Kapardis, Maria; Clark, Colin; Zopiatis, Anastasios (My University, 2016)
Purpose – Public information disclosure is a manifestation of transparency and contributes to governance-by-disclosure. Also, better financial reporting can improve the credibility and integrity of public finances and contribute to a better management of public resources. A survey was carried out in Cyprus of users’ of public financial reports concerning an expectation gap about the types of information included in such reports (information needs expectation gap) as well as the quality of such information (information quality satisfaction gap). The paper aims to discuss these issues. Design/methodology/approach – Two focus groups of users and preparers of public financial reports were used to construct the questionnaire. Users of such reports, who belonged to all three categories of public sector financial reporting identified by IPSASB, were surveyed. The quantitative data obtained was analysed using SPSS and quadrant analysis to answer the research questions posed. Findings – Data from 101 respondents confirmed that each of the information needs identified in the IPSASB Consultation Paper (2008) was rated as being a significant information need. Data analysis also showed that both types of expectation gap exist, especially as far as local authority and semi-public organisations are concerned. Research limitations/implications – The response rate in the self-administered survey was admittedly rather low but it was not unexpected mainly due to the survey’s very specialised nature and the tendency by people in Cyprus not to critique public bodies. Practical implications – Deficient financial public sector reporting means the auditor general is not able to adequately express an opinion on public spending at the local government level. This, in turn, means taxpayers do not get the quality of services they pay for. At the same time, the lack of information transparency means corrupt practices are not eradicated. One answer to the problem would be legislating the content of public financial reports. Social implications – The lack of governance-by-public exposure means that services to the local community cost a lot more, due to corruption and inefficiency. In addition, it contributes to lowering market confidence and eventually contributes to financial crisis at the national level. Originality/value – The survey conducted was the first of its kind in Cyprus to investigate financial public sector reporting and document both manifestations of the expectation gap. In addition, information needs identified in the IPSASB Consultation Paper (2008) was rated as significantly needed and this is the first time it has been done in Eurozone member state and in a country facing a financial crisis.
Keywords: Cyprus; Quadrant analysis; Financial reporting; Public sector; User satisfaction